Prática dialógica de leitura na universidade: uma contribuição para a formação do leitor responsivo e do professor letrador - Santos, Dalve Oliveira Batista (2018)
This study investigates the dialogic literacy practice known as Group Think-Aloud - GTA (ZANOTTO, 1995; 2014), that potentially advances both responsive readers’ and literacy-teaching educators’ development. The specific objectives of GTA are: a) to identify the conceptualization of reading articulated by the research participants; b) to investigate if the reading practice of GTA with a university focus group can contribute to the development of responsive and critical readers; and c) to analyze mediation and management actions of the teacher/researcher who teach readers to be responsive and critical and to examine the teacher’s instruction as literacy-teaching agent. Inherent to these objectives are the questions this study seeks to answer: 1. How do the research participants conceptualize reading? 2. Can the practice of GTA reading with a university focus group contribute to the development of responsive and critical readers? 3. How do teacher who has the aim of educating readers to be responsive and critical mediate and manage the voices of readers in group, and how have the teacher transformed as literacy-teaching agents? The underlying theory rests on studies concerning literacy practice, reading and the epistemology of language and communication from a dialogic perspective. This study employed a qualitativeinterpretive methodology (MOITA LOPES, 2006), and the methodological instruments used included Think Aloud in Groups as a method, reading diaries, and interviews. The research participants consisted of five instructors from the Freshman Support Program (PADI), students from the Literature and Linguistics Program at Tocantins Federal University. The GTA theoretical framework was used to analyze the responses to the questions posed. This study predicates participants build their academic literacy to the extent they assume the role of protagonist – that is to say, when their voices are heard and legitimated – in constructing multiple meanings during GTA practice. The data showed readers, in GTA practice, tasked themselves with being responsive and active readers. It further showed – through participants’ actions (refuting, accepting, expanding on ideas) – academic literacy improved as participants read critically, taking stands on the meanings they ascribed to texts. Moreover, the data showed how teacher developed as literacy-teaching agents inasmuch as they managed and mediated the participants